2008
DOI: 10.4018/jthi.2008040104
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Information Privacy Concerns and Computer Self-Efficacy

Abstract: Individuals have two types of focus involving privacy and technology: a person’s concerns with organizational practices towards the privacy of personal information (management focus), and the person’s self-efficacy of computers (technology focus). People view management of personal information and information technology as unrelated issues. The authors hypothesize that there is no relationship between a person’s concerns for information privacy (management focus) and his/her self-efficacy towards computers (te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Data privacy comes onto the scene in this period – a concept that is often concerned with consent and regulatory obligations in respect of personal information. Although data acquisition has been technically defined as the process of ‘sampling signals that measure real world physical conditions and converting the resulting samples into digital numeric values that can be manipulated by a computer’, it would appear that White et al (2008: 12) were using this term in its everyday sense, such as information acquisition/creation. The observation by Donkor and Nwagwu (2019) that a major component of PIM is information creation, acquisition, storage and retrieval resonates here.…”
Section: Resultsmentioning
confidence: 99%
“…Data privacy comes onto the scene in this period – a concept that is often concerned with consent and regulatory obligations in respect of personal information. Although data acquisition has been technically defined as the process of ‘sampling signals that measure real world physical conditions and converting the resulting samples into digital numeric values that can be manipulated by a computer’, it would appear that White et al (2008: 12) were using this term in its everyday sense, such as information acquisition/creation. The observation by Donkor and Nwagwu (2019) that a major component of PIM is information creation, acquisition, storage and retrieval resonates here.…”
Section: Resultsmentioning
confidence: 99%
“…Extant literature on the relationship between self-efficacy and privacy concerns is inconclusive. Some previous research has found no relationship between self-efficacy and privacy concerns (Youn, 2009;White et al, 2008;Dillon and Lending, 2010). Others have found a positive relationship between self-efficacy and privacy concerns (Mohamed and Ahmad, 2012;Chai et al, 2009).…”
Section: Social Media Self-efficacymentioning
confidence: 93%
“…Several studies (Malhotra, Kim, & Agarwal, 2004;Metzger, 2004;Phelps, Nowak, & Ferrel, 2000;Anton, Earp, He, Stufflebam, Bolchini, & Jensen, 2004) have shown that if consumers' privacy concerns are not understood and mitigated, they can have negative consequences on e-commerce growth and Internet purchases. White et al (2008) studied the relationship between computer self-efficacy and information privacy concerns. Their study focused on computer self-efficacy and its relationship with four information privacy components (collection of data, errors (data integrity), unauthorized secondary use, and improper access to data) as defined by Smith, Milberg, and Burke (1996).…”
Section: Problem Statementmentioning
confidence: 99%
“…They did not study the differences of relationships between information privacy concerns and computer self-efficacy among different age groups and genders. White et al (2008) stressed the need to extend their work by examining the differences of the relationships among different age groups and between genders. The goal of this study is to extend their work by investigating differences among different age groups and between genders regarding information privacy concerns and their relationships with computer self-efficacy.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation